Selected issues in injury and illness prevention and the team physician: A consensus statement (Medicine & Science in Sports & Exercise, 2016)
Prevention of injury and illness associated with athletic activity is one of the roles of the team physician (10,15). This process involves understanding the pathophysiology of the injury or illness, evaluating the known risk factors that influence the incidence of injury or illness, implementing interventions to minimize the influence of the risk factors, and recording the outcomes of the interventions.